(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study focuses on the Factors that significantly improve Communication Skills in the Hospitality Industry: An analysis of Grade 12 Home economics students. The Researchers selected fifty (50) students of Bestlink College of the Philippines as respondents to answer the self-made questionnaire through the distribution of Google Forms Survey. This paper is a qualitative study using a structured questionnaire to collect participant data. By the answers of the respondents, researchers can determine the collected data. This study examines the factors that play a significant role in improving communication skills in the Hospitality Industry. The study proved that to provide good services, the students agreed to the factors that may help improve communication skills. This study recommends that the students must also do their part as students to fulfil the skills needed to improve and comply with the simulation task.